2022
DOI: 10.1021/acsenergylett.2c01484
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Copper-Doped Perovskite-Related Silver Halide X-ray Imaging Scintillator

Abstract: Scintillators are critical for high-energy radiation detection across a wide array of potential applications, from medical radiography and safety inspections all the way to space exploration. However, constrained by their current shortcomings, including high-temperature and complex fabrication as well as inherent brittleness and fragility among thick films and bulk crystals, traditional scintillators are finding it difficult to meet the rising demand for cost-effective, ecofriendly, and flexible X-ray detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 45 publications
2
72
0
Order By: Relevance
“…Materials such as CsI (CsI:TI), LYSO (Lu,Y) 2 SiO 5 :Ce 3+ ), and GOS (Gd 2 O 2 S:Tb 3+ ) are currently widely used as scintillators in indirect X-ray detectors. However, they have several limitations such as complicated synthesis processes and poor thermal stability. Recently, lead halide perovskites (LHPs) have attracted significant attention as scintillators due to their low detection limits and the possibility of multicolor radioluminescence (RL). However, the main drawbacks of the LHPs as scintillators are low thermal and chemical stability and self-absorption properties of LHPs. Moreover, the inherent toxicity of lead is a critical limitation of LHPs. Recently, lead-free metal halides have been developed as scintillators. , For instance, Yang et al reported that Rb 2 CuBr 3 was as a scintillator with a high light yield and Zhang et al applied Rb 2 AgBr 3 , with its short scintillation decay time, to dynamic X-ray imaging . In addition, Jiang et al applied C 4 H 12 NMnCl 3 and (C 8 H 20 N) 2 MnBr 4 for a WLED and X-ray scintillator .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Materials such as CsI (CsI:TI), LYSO (Lu,Y) 2 SiO 5 :Ce 3+ ), and GOS (Gd 2 O 2 S:Tb 3+ ) are currently widely used as scintillators in indirect X-ray detectors. However, they have several limitations such as complicated synthesis processes and poor thermal stability. Recently, lead halide perovskites (LHPs) have attracted significant attention as scintillators due to their low detection limits and the possibility of multicolor radioluminescence (RL). However, the main drawbacks of the LHPs as scintillators are low thermal and chemical stability and self-absorption properties of LHPs. Moreover, the inherent toxicity of lead is a critical limitation of LHPs. Recently, lead-free metal halides have been developed as scintillators. , For instance, Yang et al reported that Rb 2 CuBr 3 was as a scintillator with a high light yield and Zhang et al applied Rb 2 AgBr 3 , with its short scintillation decay time, to dynamic X-ray imaging . In addition, Jiang et al applied C 4 H 12 NMnCl 3 and (C 8 H 20 N) 2 MnBr 4 for a WLED and X-ray scintillator .…”
mentioning
confidence: 99%
“…13−16 Recently, lead-free metal halides have been developed as scintillators. 17,18 For instance, Yang et al reported that Rb 2 CuBr 3 was as a scintillator with a high light yield 19 and Zhang et al applied Rb 2 AgBr 3 , with its short scintillation decay time, to dynamic Xray imaging. 20 In addition, Jiang et al applied C 4 H 12 NMnCl 3 and (C 8 H 20 N) 2 MnBr 4 for a WLED and X-ray scintillator.…”
mentioning
confidence: 99%
“…A short lifetime was required for dynamic X-ray imaging. Both the broad emission and large Stokes shift were probably due to self-trapped exciton (STE) emission, while the lifetime was obviously short. , We thus propose the defect-bound excitons (DBEs) radioluminescence of our Rb 2 AgCl 3 scintillator, corresponding to that of the Rb 2 AgBr 3 …”
Section: Resultsmentioning
confidence: 87%
“…Both the broad emission and large Stokes shift were probably due to self-trapped exciton (STE) emission, while the lifetime was obviously short. 24,25 We thus propose the defect-bound excitons (DBEs) radioluminescence of our Rb 2 AgCl 3 scintillator, corresponding to that of the Rb 2 AgBr 3 . 26 To explore the reason for broadband emission, different wavelengths were applied to investigate PLE spectra of the Rb 2 AgCl 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, perovskites acting as scintillators have aroused huge attention. Particularly, the unique connectivity structure of zero-dimensional (0D) perovskites induces strong exciton localization and electron–phonon interaction, leading to characteristic emissions such as a broad symmetrical emission band, self-absorption free, and long lifetime. Additionally, the 0D perovskites have been described as ideal candidates for X-ray detection scintillators on account of the merits, including easy preparation, high stability, and reabsorption-free radioluminescence (RL). Copper-based scintillators have been extensively studied as typical zero-dimensional scintillators, achieving a high light yield and high spatial resolution of 17 lp·mm –1 . , …”
Section: Introductionmentioning
confidence: 99%